PERHITUNGAN MATEMATIKA DASAR BERBASIS MULTIMEDIA MENGGUNAKAN METODE JARIMATIKA - novitasari ballo (Jurnal Teknologi Terpadu, 2016)
Progress in science and engineering bring about the changes in human life in almost all aspectsof life. Education the prevailing current started from the level of education the ground level. One ofeducation the ground level thet develops is primary school (SD). In matters of basic mathematicalcalculation. Math is one of the lesson the important primary school. Currently has been developing allkinds of methods to count. In essence all those methods is good, all the entitled to studies techniquesand children primary school rich in a technique. One method that have evolved to math especially incount is teaching jarimatika method. A jarimatika method is one way to count by using the tools thefingers. With the jarimatika methods students of trained for memorization calculation basicmathematical. The use of a method of jarimatika in a calculation on the mathematics can ease primaryschool student in learning a summation, the reduction of, multiplication, and division. This needs tothe knowing jarimatika method made in the form of multimedia namely interactive multimedia basicmathematical uses the jarimatika method. Interactive multimedia was created using MacromediaFlash 8. The Interactive multimedia made will be applied on primary schools Inpres Oebufu. TheInteractive multimedia is made to ease students in learn math and ease teaching and creating alearning more interesting.